ANALISIS EFISIENSI PEMASARAN EMPING MELINJO DI KELURAHAN SUKAMAJU KECAMATAN TELUK BETUNG TIMUR KOTA BANDAR LAMPUNG - Tsuraya Khairunnisa; Muhammad Irfan Affandi; Ani Suryani (Lampung University, 2018)
This research aims to analyze the efficiency of marketing channels and margins of melinjo chips in Sukamaju village, Teluk Betung Timur Subdistrict, Bandar Lampung City. The research is conducted by survey method, in which location is determined purposively. Respondents of this research, producers of melinjo chips in Sukamaju village of Teluk Betung Timur, Bandar Lampung, are drawn by simple random sampling method. This research uses analysis method of marketing channel, margin producer's share analysis, and price transmission elasticity. The results of this study indicated that there were two types of marketing channels in Sukamaju village. The first channel was producer to consumer, and secondly was producer to retailer then consumer. The marketing of melinjo chips in Sukamaju village had a margin percentage and a market share of 42.00% and 58.00% on channel I; of 33.33% and 66.67% on channel II respectively. Marketing of melinjo chips had been economically efficient with competing margin percentage, but based on Price Transmission Elasticity (Et) marketing system was not efficient with Et by 1,13 (Et >1).Key words: efficiency, margin, marketing channels, melinjo chips